2008
DOI: 10.1001/archotol.134.5.470
|View full text |Cite
|
Sign up to set email alerts
|

Major Salivary Duct Clipping for Control Problems in Developmentally Challenged Children

Abstract: Objectives: To introduce a technical modification for interruption of the parotid and submandibular salivary ducts and to demonstrate the technique's effectiveness and effect on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
5
27
0
Order By: Relevance
“…Accessory openings along the ducts may also explain why some patients had limited long-term benefit from surgery. In addition, intra-operative probing of the duct may cause a false passage or trauma to the duct and subsequent fistula formation [10]. In accordance with these proposed mechanisms of recurrence, we found upon re-exploration of 2 patients, that the new duct openings were present in locations distant from the native position of the papilla.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Accessory openings along the ducts may also explain why some patients had limited long-term benefit from surgery. In addition, intra-operative probing of the duct may cause a false passage or trauma to the duct and subsequent fistula formation [10]. In accordance with these proposed mechanisms of recurrence, we found upon re-exploration of 2 patients, that the new duct openings were present in locations distant from the native position of the papilla.…”
Section: Discussionsupporting
confidence: 79%
“…These results are comparable to ours, with drooling recurring in the majority of patients over a short time. Recently, El-Hakim et al [10] published a modification of the surgical technique with good control of drooling with followup over 2-18 months. He recommended the use of vascular clips instead of sutures to ligate the ducts and avoidance of canulation of the ducts which may lead to damage to the duct and leakage of saliva at this weak point.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment of excessive saliva production in neurologically impaired children results in improvement of respiratory symptoms. [22][23][24] This study showed no association between lipid laden macrophage index and BAL amylase. This lack of correlation could be due to differences in accuracy between the two tests.…”
Section: Figmentioning
confidence: 54%
“…Overall the median GCBI for children receiving SMD was 19.5. This was elevated in the RAST positive group (median score 27) and lower for the RAST negative group (median score 14). Conclusion: This study highlights some benefit to inferior turbinate study in children by using the GCBI.…”
Section: Methodsmentioning
confidence: 64%
“…In context with other ENT surgical procedures such as adenotonsillectomy [7], salivary duct clipping [14] for drooling and bone anchored hearing aid [8], GCBI scores are 21, 33 and 54, respectively. Currently, there is no consensus on defining a population of individuals who will benefit from SMD.…”
Section: Discussionmentioning
confidence: 99%